A Capable Surgeon and a Willing Electrologist: Challenges to the Expansion of Transgender Surgical Care in the United States. (27th February 2019) - Plemons, Eric
Abstract: Since 2014, public and private insurance coverage for transgender Americans' surgical care has increased exponentially. Training clinicians and equipping institutions to meet the surge in demand has not been as rapid. Through ethnographic research at a surgical workshop focused on trans‐ genital reconstruction and in a U.S. hospital working to grow its transgender health program, this article shows that effects of the decades‐long insurance exclusion of trans‐ surgery are not easily remedied through the recent event of its inclusion because patient access is not the only thing that has been restricted by coverage denial. Decades of excluding coverage for trans‐ genital reconstructive surgery have limited the development and circulation of technical skills required to perform these procedures, as well as the administrative processes needed to integrate them into existing clinical workflows. One surgeon estimates that turning expanded access into realized care is "a five or six‐year problem."